The truth about the 1st cycle Coulombic efficiency of LiNi1/3Co1/3Mn1/3O2 (NCM) cathodes. Issue 5 (15th January 2016) - Kasnatscheew, J.; Evertz, M.; Streipert, B.; Wagner, R.; Klöpsch, R.; Vortmann, B.; Hahn, H.; Nowak, S.; Amereller, M.; Gentschev, A.-C.; Lamp, P.; Winter, M.
Abstract : High voltage issues of the NCM cathode could be attributed predominantly to structural instabilities and unexpected negligible electrolyte oxidation. Abstract : The 1st cycle Coulombic efficiency (CE) of LiNi1/3 Co1/3 Mn1/3 O2 (NCM) at 4.6 V vs. Li/Li + has been extensively investigated in NCM/Li half cells. It could be proven that the major part of the observed overall specific capacity loss (in total 36.3 mA h g −1 ) is reversible and induced by kinetic limitations, namely an impeded lithiation reaction during discharge. A measure facilitating the lithiation reaction, i.e. a constant potential (CP) step at the discharge cut-off potential, results in an increase in specific discharge capacity of 22.1 mA h g −1 . This capacity increase during the CP step could be proven as a relithiation process by Li + content determination in NCM via an ICP-OES measurement. In addition, a specific capacity loss of approx. 4.2 mA h g −1 could be determined as an intrinsic reaction to the NCM cathode material at room temperature (RT). In total, less than 10.0 mA h g −1 (=28% of the overall capacity loss) can be attributed to irreversible reactions, mainly to irreversible structural changes of NCM. Thus, the impact of parasitic reactions, such as oxidative electrolyte decomposition, on the irreversible capacity is negligible and could also be proven by on-line MS. As a consequence, the determination of the amount of extracted Li + ("Li + extraction ratio") so far has been incorrect and must be calculated by the charge capacity (=delithiation amount) divided by the theoretical capacity. In a NCM/graphite full cell the relithiation amount during the constant voltage (CV) step is smaller than in the half cell, due to irreversible Li + loss at graphite.